Effects of the cognitive tasks in the postural control of elderly: A systematic revision - Larissa Pires de Andrade; Florindo Stella; Fábio Augusto Barbieri; Natália Madalena Rinaldi; Ágata Yoko Yasue Hamanaka; Lilian Teresa Bucken Gobbi (Desafio Singular, 2011)
Demanding attention in order to keep postural balance increases with aging and with the presence of concurrent tasks that require information processing. Several studies have demonstrated that motor performance can be related to the complexity of the task and aging process, presenting a possible interaction between these factors. The aim of this review was to identify and analyze published papers about the effects of cognitive tasks on the postural control of elderly individuals. A systematic search in the Web of Science, SportDiscus, CINAHL, Science Direct on line, Biological Abstracts, PsycINFO, and Medline databases was made and 444 articles were found. Eight were selected that studied the variables of interest. These studies showed that postural control seems to be influenced by the individual's attention processes and that deficits in such ability may be associated to an increased risk of falls.